2004
DOI: 10.1785/012003154
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Velocity and Attenuation Structure of the East Rift Zone and South Flank of Kilauea Volcano, Hawaii

Abstract: It has been proposed that a deep magma body beneath the east rift zone (ERZ) of Kilauea volcano, Hawaii, must be present in order to explain the observed deformation of the south flank. From November 1999 to June 2000, 29 IRIS-PASSCAL three-component seismographs were operated across Kilauea's ERZ and south flank. Using local earthquakes recorded by these stations, supplemented with data from the Hawaiian Volcano Observatory stations, we investigated the deep structure of the ERZ and south flank through two ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 36 publications
6
62
0
Order By: Relevance
“…One of the main differences between this study and previous ones is the improved V p model resolution at deeper layers owing to the inclusion of events with large epicentral distances and application of the composite event method. Our V p model is well resolved to 20 km depth near the volcano calderas and their rift zones ( Figure 6) and generally agrees with the previous models [Ryall and Bennett, 1968;Hill, 1969;Ellsworth and Koyanagi, 1977;Zucca and Hill, 1980;Thurber, 1984;Rowan and Clayton, 1993;Okubo et al, 1997;Dawson et al, 1999;Haslinger et al, 2001;Hansen et al, 2004;Monteiller et al, 2005;Park et al, 2007;Got et al, 2008;Park et al, 2009;Syracuse et al, 2010]. The common features observed in these studies and also in our model are the high-velocity anomalies in the upper 9 km depth beneath Kilauea caldera and its rift zones, indicative of magma cumulates.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…One of the main differences between this study and previous ones is the improved V p model resolution at deeper layers owing to the inclusion of events with large epicentral distances and application of the composite event method. Our V p model is well resolved to 20 km depth near the volcano calderas and their rift zones ( Figure 6) and generally agrees with the previous models [Ryall and Bennett, 1968;Hill, 1969;Ellsworth and Koyanagi, 1977;Zucca and Hill, 1980;Thurber, 1984;Rowan and Clayton, 1993;Okubo et al, 1997;Dawson et al, 1999;Haslinger et al, 2001;Hansen et al, 2004;Monteiller et al, 2005;Park et al, 2007;Got et al, 2008;Park et al, 2009;Syracuse et al, 2010]. The common features observed in these studies and also in our model are the high-velocity anomalies in the upper 9 km depth beneath Kilauea caldera and its rift zones, indicative of magma cumulates.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…Poland et al [2013] suggested that the increased supply at Pu'u 'O'o-Kupaianaha during 2003-2007 must have been driven by increased flux of magma from the mantle, which is supported by increased CO 2 emissions. The low-V p and low-V p ∕V s anomalies observed in our model are consistent with the existence of CO 2 and were also observed by Hansen et al [2004]. The resolved area in the lower ERZ has one high-and one low-V p ∕V s body next to each other.…”
Section: Kilauea Volcanosupporting
confidence: 90%
See 3 more Smart Citations